Initial Low-Density Lipoprotein Cholesterol and Inflammation Status Predicts Long-Term Mortality in Patients with Acute Coronary Syndrome in the Chinese Population - Yanqiao Lu; Yujun Sun; Yutong Miao; Zhitong Liu; Lan Shen; Ben He (Biomedicines)
Background: Low-density lipoprotein cholesterol (LDL-C) is considered an important risk factor for acute coronary syndrome (ACS). Recent studies have revealed high mortality in ACS patients with low LDL-C levels. However, the association between spontaneously very low LDL-C levels and the prognosis in ACS remains unknown. Methods: A total of 1882 consecutive statin-null ACS patients were analyzed and categorized into four groups according to their on-admission LDL-C level: very low <70 mg/dL, low 70–99 mg/dL, high 100–129 mg/dL, and very high ≥130 mg/dL. In-hospital mortality and 3-year mortality were assessed. Among them, 1009 patients were further grouped according to the hs-CRP value (<2 mg/L and ≥2 mg/L). Results: Over one-third of the patients had an initially lower LDL-C concentration. Higher in-hospital mortality (9.7%, 4.5%, 2.7%, and 3.5%, p = 0.001), long-term mortality (20.8%, 13.1%, 8.0%, and 7.8%, p < 0.001), and lower survival rate (KM: HR = 3.15, 95% CI 1.40–7.12, p < 0.001; Cox: HR = 2.09, 95% CI 1.30 to 3.36) were observed in the very low LDL-C group compared with other groups. Patients in the low LDL-C high CRP subgroup had the worst prognosis compared with other subgroups (in-hospital: 7.7%, 1.2%, 0.5%, and 4.3%, p = 0.031; long-term: 15.5%, 1.2%, 2.6%, and 9.4%, p = 0.018). Lower LDL-C levels were accompanied by higher CRP levels (p = 0.003). The CRP–LDL-C ratio had good predictive ability on short-term and long-term outcomes (AUC: 0.630 and 0.738). Conclusions: Spontaneously very low LDL-C level was independently associated with poor long-term survival in patients with ACS. Lower LDL-C level was related to higher CRP level, while the CRP–LDL-C ratio may be a potential risk prediction factor.